Teaching English through Gaming to Increase Students’ Speaking Skill at Junior High School - Nuriyanti, Ika (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this study is to determine how well SMP Muhammadiyah 06 DAU students' speaking abilities can be enhanced by using game as method. The students' speaking abilities improve as a result of these advancements. Prior to putting the activities into practice. Data from performance tests, student observations, and implementation discussions are analyzed using the qualitative technique. Student opinions about the use of gaming in English language learning, particularly speaking skills, are also processed. The outcome showed that using game content to improve students' speaking abilities is thought to be highly successful. The students' speaking abilities improve as a result of these advancements. Prior to putting the activities into practice, according to the observations, student activity increased from an average of 74,7% in cycle one and 82.2% in cycle two to 86.3% in cycle three. Additionally, speaking proficiency in the learning process increased from 75.7% in cycle I to 87.8% in cycle II to 93.8% in cycle III. It was stated that game method was an innovation in English language instruction that helped students relax and enjoy the process while also dispelling the myth that learning English is hard. Gaming is not only attract students' interest but is also able to maintain student activity in the learning process. The use of gaming in junior high schools has also been proven to make class time more efficient because the material delivered and targeted achievements can be achieved according to schedule. There is no doubt that it improves pupils' confidence, active engagement, and speaking fluency.